"The Impact of Organizational Justice on Knowledge Sharing: Testing the Mediating Role of Job Satisfaction A Case Study of Algeria Telecom Annaba - " - Hamza Baali (Journal of Excellence for Economics and Management Research, 2026)
The study aimed to highlight the impact of organizational justice on knowledge sharing, considering job satisfaction as a mediating variable, from the perspective of employees at Algeria Telecom, the study relied on both descriptive and analytical approaches, to achieve its main objective, a sample of 117 individuals was collected, and statistical methods such as regression and path analysis were used, the results showed a positive effect among the study variables, with a weak but positive indirect effect between organizational justice and knowledge sharing, The study recommends adopting fair organizational policies by promoting transparent practices in evaluation and distribution, as well as creating a work environment that supports job satisfaction, which in turn enhances knowledge sharing among employees.